AUTOMATION OF CONTROL OF THE BUSINESS PROCESS OF PUBLISHING SCIENTIFIC JOURNALS - O. Yu. Sakaliuk (Автоматизация технологических и бизнес-процессов, 2016)
We consider business process automation publishing scientific journals. It describes the focal point of publishing houses Odessa National Academy of Food Technology and the automation of business processes. A complex business process models publishing scientific journals. Analyzed organizational structure of Coordinating Centre of Scientific Journals' Publishing ONAFT structure and created its model. A process model simulation conducted business process notation eEPC and BPMN. Also held database design, creation of file structure and create AIS interface. Implemented interaction with the webcam. Justification feasibility of software development, and the definition of performance based on the results petal chart, it is safe to say that an automated way to much more efficient compared to manual mode. The developed software will accelerate the development of scientific periodicals ONAFT, which in turn improve the academy ratings at the global level, improve its image and credibility.